Sustainable machining of the magnesium alloy materials in the CNC lathe machine and optimization of the cutting conditions - BAKIR, BARKIN; EKİCİ, BÜLENT; KURT, MUSTAFA (KAUNAS UNIV TECHNOL, 2014)
In this study, MQL turning performance was compared to dry conditions. The magnesium based material will be formed by applying the orthogonal cutting. The CNC Lathe shall be used for both cutting processes. The experiment used MINITAB 16 software to establish the experiment plan. In this study, workpiece was turned at cutting speeds of 230, 330 and 430 m/min, feed rates of 0.20, 0.35 and 0.50 mm/rev and cutting depth of 1, 2 and 3 mm. Taguchi experimental design method was used for determining the settings of turning parameters. Orthogonal arrays of Taguchi, the signal-to-noise (S/N) ratio, the analysis of variance (ANOVA) were carried out to determine the optimum levels and to analyze the influence of cutting speed, feed rate, cutting depth on surface roughness, temperature and cutting forces during dry and MQL turning.
Keywords: Dry turning; MQL (Minimum Quantity Lubrication); Magnesium; Signal to Noise Ratio; ANOVA (Analysis of Variance); DRY